Perancangan Infografis Animasi “Ayo Cuci Tangan” Sebagai Upaya Pencegahan Penyebaran Covid -19 Untuk Anak Usia 9 – 13 Tahun Di Kota Bandung Oleh Dinas Kesehatan Kota Bandung - Nichi Hana Karlina; Windy Juliani (Universitas Informatika dan Bisnis Indonesia, 2020)
At the end of 2019, many countries including Indonesia were hit by the COVID-19 pandemic caused by the corona virus. The Ministry of Health, especially the Bandung City Health Office, has recommended several efforts that can be made by the community to avoid the transmission of the corona virus, one of which is washing hands. Good and correct hand washing behavior for children is still lacking, because many media information about hand washing still focus on adults so that it is less effective for children. Seeing the tendency of children to learn and how to get information at this time using digital media, an animated infographic was designed on the steps for washing hands specifically for children especially for children 9-13 years. This type of research is a qualitative research. The data of this research are qualitative data so that the data are in a substantive category which is then interpreted with references to scientific references. With the creation of animated infographics, it is hoped that children will be more interested and easier to understand the information on good and correct handwashing steps, and the information conveyed in this information media can be applied in everyday life.